IDENTIFIKASI JENIS-JENIS SAMBUNGAN PADA KONSTRUKSI RUMAH PANGGUNG DI SAMARINDA - Kusno Yuli Widiati; Maretha Silvana Hartanti (ULIN: Jurnal Hutan Tropis, 2019)
The existence of a house on stilts when compared to residential houses of concrete can be said to be more environmentally friendly, especially in water catchment areas or marshy. However, the number of houses on stilts is decreasing. This is because the stigma of stilt houses which are generally made of wood is an average house for the lower classes, especially in urban areas. In addition to being more environmentally friendly, the stage house also has its own uniqueness, one of which is the shape and type of connections used to extend the dimensions of the wood material used. Therefore, to enrich the existing information, this study aims to identify the types of connections in the upper girder and stage bottom girders so that it is expected to help further research in the related field of research. This research uses descriptive qualitative method by using photo documentation and conducting interviews as supporting data. The results showed that there were several types of joints but generally used the connection of mortise and tenon, half lap, scarf joint, scarf joint with under-squinted ends and scarf joint with wedges which were aided by pegs, bolts and wood clamps.